Elemental composition of Malawian rice - Joy, Edward J.M.; Louise Ander, E.; Broadley, Martin R.; Young, Scott D.; Chilimba, Allan D.C.; Hamilton, Elliott M.; Watts, Michael J. (Springer, 2017)
Widespread potential dietary deficiencies of calcium (Ca), iron (Fe), iodine (I), selenium (Se) and zinc (Zn) have been identified in Malawi. Several deficiencies are likely to be compounded by high phytic acid (PA) consumption. Rice (Oryzasativa) is commonly consumed in some Malawian populations, and its mineral micronutrient content is important for food security. The considerable irrigation requirements and flooded conditions of paddy soils can also introduce or mobilise potentially toxic elements including arsenic (As), cadmium (Cd) and lead (Pb). The aim of this study was to determine the mineral composition of rice sampled from farmers’ fields and markets in Malawi. Rice was sampled from 18 extension planning areas across Malawi with 21 white (i.e. polished) and 33 brown samples collected. Elemental composition was determined by inductively coupled plasma-mass spectrometry (ICP-MS). Arsenic speciation was performed using high-performance liquid chromatography (HPLC)-ICP-MS. Concentration of PA was determined using a PA-total phosphorus assay. Median total concentrations (mg kg−1, dry weight) of elements important for human nutrition in brown and white rice, respectively, were: Ca = 66.5 and 37.8; Cu = 3.65 and 2.49; Fe = 22.1 and 7.2; I = 0.006 and <0.005; Mg = 1130 and 265; Mn = 18.2 and 9.6; Se = 0.025 and 0.028; and Zn = 17.0 and 14.4. In brown and white rice samples, respectively, median PA concentrations were 5438 and 1906 mg kg−1, and median PA:Zn molar ratios were 29 and 13. Concentrations of potentially toxic elements (mg kg−1, dry weight) in brown and white rice samples, respectively, were: As = 0.030 and 0.006; Cd ≤ 0.002 and 0.006; Pb = 0.008 and 0.008. Approximately 95 % of As was found to be inorganic As, where this could be quantified. Malawian rice, like the more widely consumed staple grain maize, contains inadequate Ca, I, Se or Zn to meet dietary requirements. Biofortification strategies could significantly increase Se and Zn concentrations and require further investigation. Concentrations of Fe in rice grain varied greatly, and this was likely due to contamination of rice samples with soil. Risk of As, Cd or Pb toxicity due to rice consumption in Malawi appears to be minimal.